The features of Change in Land Usages Map at Alhanakiah City during the period from 1990-2020 using Remote Sensor Technologies - Alharbi, Shuded Ali; Alshabaan, Ahmed Mohammed (Journal of Humanities & Social Sciences, 2023)
The land usages have been varied at Alhanakiah City due to the population growth the city has witnessed since 1990, where the development aspects reached most of the Kingdom cities which are going through sequence developmental plans in the Kingdom. The study aimed to utilize remote sensor technologies in detecting the change that occurred in the land usages. The study sought to fulfill a group of objectives, the most eminent of which are: casting the most important change features on the map of the land usages in the city during the period from (1990 up to 2020). To recognize the current urban development directions at Alhanakiah city. The study used the spatial analysis method to utilize remote sensor technologies in detecting the change that occurred in the land in order to reach to the most important results. To achieve its objectives, the study used some of the spatial statistic methods such as the integration of domains for the satellite visual, cropped the visual within the study field limits, conducting the oriented classification, detecting the change for the study region through combine tool for the integration of the layers. The study reached to the highest rates of change in the land coverage in the study region during the period from 1990 up to 2020, and they were in favor of the urban regions on the account of the rocky outcrops with (4.08%). Finally, the study recommends to cast the changes in the land usages between different periods using the remote sensor techniques.
Keywords: Land Usages Map; Al-Hanakiyah city; remote sensing technology; population growth; Saudi Arabia